Unmet medical needs and future perspectives for leiomyosarcoma patients: a position paper from the National LeioMyoSarcoma Foundation (NLMSF) and Sarcoma Patients EuroNet (SPAEN) - Kasper, Bernd; Achee, Annie; Schuster, Kathrin; Wilson, Roger; van Oortmerssen, Gerard; Gladdy, Rebecca A.; Hemming, Matthew L.; Huang, Paul; Ingham, Matthew; Jones, Robin L.; Pollack, Seth M.; Reinke, Denise; et al. (Cancers, 2021)
As leiomyosarcoma patients are challenged by the development of metastatic disease, effective systemic therapies are the cornerstone of outcome. However, the overall activity of the currently available conventional systemic treatments and the prognosis of patients with advanced or metastatic disease are still poor, making the treatment of this patient group challenging. Therefore, in a joint effort together with patient networks and organizations, namely Sarcoma Patients EuroNet (SPAEN), the international network of sarcoma patients organizations, and the National LeioMyoSarcoma Foundation (NLMSF) in the United States, we aim to summarize state-of-the-art treatments for leiomyosarcoma patients in order to identify knowledge gaps and current unmet needs, thereby guiding the community to design innovative clinical trials and basic research and close these research gaps. This position paper arose from a leiomyosarcoma research meeting in October 2020 hosted by the NLMSF and SPAEN.